Acción de las organizaciones sociales de base territorial - ROFMAN, Adriana (UNIVERSIDAD NACIONAL GRAL.SARMIENTO, 2002)
Otros autores: ACCINELLI, Mariana; BALAN, Eduardo; CALELLO, Tomás; LOZANO, Claudio; QUINTAR, Aida; REBORATTI, Laura